PENGGUNAAN METODE CERAMAH DAN DEMONTRASI PADA PEMBELAJARAN TARI BEDANA SISWA KELAS VIII.1 SMP NEGERI 1 MARGATIGA KABUPATEN LAMPUNG TIMUR - Febrilyan Sakuntala Devi; Hasyimkan Hasyimkan; Susi Wendhaningsih; Fitri Daryanti (Jurnal Seni dan Pembelajaran, 2013)
AbstractThis research aimed to describe the implementation of lecturing and demonstration method and the its result on Bedana dance teaching learning at the VIII.1 class of SMPN 1 Margatiga, East Lampung.The research method used in this research was qualitative descriptive by using lecturing and demonstration method. The data in this research was taken from the art and culture teacher in that school and from the VIII.1 class which consisted of total 36 students, in which there were 14 male students and 22 female students, The collecting data techniques used in this research were observation, documentation, and interview. The research instruments of this research were practical test, students‟ activities observation, and teacher‟s activities observation.The use of lecturing and demonstration method in teaching Bedana dance is related each other. Lecturing and demonstration have their own part. Lecturing method in teaching Bedana dance was used by the teacher in explaining history material, function, developing and explaining 9 gesture kinds of Bedana dance, meanwhile demonstration method to be used for demonstrating 9 gesture kinds of Bedana dance that istahtim, khesek gantung, khesek injing, jimpang, humbak molo, ayun, gantung, belitut dan gelek. In conducting lecturing and demonstration method in teaching Bedana dance have more and lack. The more of lecturing and demonstration method was the learning is easier and interesting. Meanwhile, the lack of lecturing and demonstration method was the students‟ understanding of material just limit on what was given by the teacher because the students just accept the material that given by the teacher.The teaching result of Bedana dance at the Viii.1 Class Of SMPN 1 Margatiga consider from the ability of dance on all of the aspects include in category enough.The aspectof gesture technique include in category enough. The aspect of exact account are include in category enough. The aspect of remembering the the gesture include in category good.Key word: lecturing and demonstration method, result, education and Bedana dance